THE STUDY OF THE RUBAS FORTIFICATION IN 2020 - Gmyra, Ludmila Borisovna; Saidov, Vadim Atemovic; Magomedov, Usup Abdusalamovic (History, Archeology and Ethnography of the Caucasus, 2020)
The article proposes preliminary results of the excavations of the Rubas fortification complex of the middle 7th century in 2020. Archeological object is located in the lower reaches of the river Rubas, close to the village of Kommuna, Derbent region, Republic of Dagestan, 20 km south-west to Derbent. In 2014, 2016-2018 we conducted studies of four military-engineering structures that are part of the defense complex: 1) arched structure of a tower type; 2) stone wall № 1, attached to the arched structure from the north; 3) a monumental stone defensive wall № 2, oriented in the South – North direction (a 28 m section is revealed); 4) stone wall № 3, attached to the wall № 2 from the east, oriented in the west-east direction (section 5 was exposed). The studies of the Rubas fortification in 2020 were aimed at solving a number of problematic issues related to the planning of the defensive complex, its structure and the functional purpose of its constituent structures. A complex structure and layout of the northern section of the main wall № 2 have been determined (stepped shape, protrusion from the baseline of the eastern facade of the wall № 2 by 2.5 m, signs of rounding to the southeast). New data were obtained on the shape and construction of wall № 3 (rounded shape with a bend to the north-east, stepped structure, the use of specific techniques for installing massive blocks into the wall). A new structure was revealed in the form of a platform of 7x5 m with a bend to the northeast at 22,50. The analogies of such structures have not been established. In 2020, a fundamentally new information has been obtained on the problematic issues of the structure of the studied defensive complex, which make significant adjustments to the preliminary conclusions about the layout and design of the identified structures and the functional purpose of the Rubas fortification as a whole.